The Pedagogy of The Oppressed: Rediscovering Subjectivity in Education - Mudin, Imam; Putra, Andri Azis; Kusman, Agus; Imanulhaq, Rela (Arfannur: Journal of Islamic Education, 2025)
This article analyzes the interaction between teachers and students through the story of This study examines pedagogical transformation through a critical perspective, focusing on the deconstruction of marginalization mechanisms in contemporary education systems. Through the method of critical content analysis of academic documentation for the 2020-2024 period, the research explores how reproductive pedagogical practices limit students' subjectivity. Paulo Freire's theoretical framework of critical consciousness is used to dismantle hidden power relations in educational institutions. Studies show that education is not just a transmission of knowledge, but a complex arena of ideological battle. The research proposes the pedagogic of love and the dialogical approach as liberation strategies, in which teachers and students are equally involved in the construction of knowledge. Key recommendations include the deconstruction of an exclusive curriculum, the development of a pedagogical model that respects subjective experience, and the development of an inclusive institutional culture. The contribution of the research lies in providing an alternative conceptual framework that positions education as a transformative practice that dismantles the mechanisms of systemic oppression.